Resistance to oxidative stress by inner membrane protein ElaB is regulated by OxyR and RpoS. Issue 2 (17th January 2019) - Guo, Yunxue; Li, Yangmei; Zhan, Waner; Wood, Thomas K.; Wang, Xiaoxue
Summary: C‐tail anchored inner membrane proteins are a family of proteins that contain a C‐terminal transmembrane domain but lack an N‐terminal signal sequence for membrane targeting. They are widespread in eukaryotes and prokaryotes and play critical roles in membrane traffic, apoptosis and protein translocation in eukaryotes. Recently, we identified and characterized in Escherichia coli a new C‐tail anchored inner membrane, ElaB, which is regulated by the stationary phase sigma factor RpoS. ElaB is important for resistance to oxidative stress but the exact mechanism is unclear. Here, we show that ElaB functions as part of the adaptive oxidative stress response by maintaining membrane integrity. Production of ElaB is induced by oxidative stress at the transcriptional level. Moreover, elaB expression is also regulated by the key regulator OxyR via an OxyR binding site in the promoter of elaB . OxyR induces the expression of elaB in the exponential growth phase, while excess OxyR reduces elaB expression in an RpoS‐dependent way in the stationary phase. In addition, deletion of elaB reduced fitness compared to wild‐type cells after prolonged incubation. Therefore, we determined how ElaB is regulated under oxidative stress: RpoS and OxyR coordinately control the expression of inner membrane protein ElaB. Abstract : The elaB expression is regulated by the key regulator OxyR via an OxyR binding site in the promoter of elaB. OxyR induces the expression of elaB in the exponential growth phase, while excess OxyR reduces elaB expression in an RpoS‐dependent way in the stationary phase. In addition, deletion of elaB reduced fitness compared to wild‐type cells after prolonged incubation.